2010
DOI: 10.1111/j.1468-1331.2010.02950.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution ultrasound in the evaluation and prognosis of Bell’s palsy

Abstract: This first study utilizing US in Bell's palsy highlights its role in outcome prediction and contributes to our understanding of recovery processes in this common neurological disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 24 publications
1
32
0
2
Order By: Relevance
“…The change in HB grade was examined for any relationship with time and symptom factors, in the same manner as was done by Lo et al (21).…”
Section: Methodsmentioning
confidence: 99%
“…The change in HB grade was examined for any relationship with time and symptom factors, in the same manner as was done by Lo et al (21).…”
Section: Methodsmentioning
confidence: 99%
“…In this prospective, controlled study, patients with Bell's palsy, ultrasound was performed 2–7 days after the onset of paralysis using a General Electric Logiq 7 Pro with a 5 to 10 MHz linear array transducer [1]. Facial nerve diameter was measured proximally at the stylomastoid foramen, distally just proximal to the pes anserinus, and midway between these two points.…”
Section: Imaging Techniques For the Evaluation Of The Facial Nervementioning
confidence: 99%
“…MRI imaging is indicated later in the course of Bell's palsy if full recovery of facial function does not occur within 9 months of onset [21]. Recently, ultrasound has been utilized to predict outcomes in Bell's palsy, as discussed above [1]. …”
Section: Disorders Of the Facial Nervementioning
confidence: 99%
See 1 more Smart Citation
“…Lo et al [10] performed a prospective study of the effectiveness of high-resolution ultrasound for prognostication of recovery in Bell's palsy. They found that, although facial nerve diameter as measured on ultrasound did not correlate with clinical and neurophysiologic indicators at initial presentation, it correlated better than other measures for degree of paralysis at 3 months.…”
Section: Advances In Radiological Imagingmentioning
confidence: 99%